Are you afraid of the dark? [videorecording (DVD)] - Grabinski, BenDavid, 1983-; Kandel, Ned; MacHale, D. J. (Paramount Home Entertainment, 2020)
A nightmarish three-part limited series event filled with scorpions, eyeless men, disappearing children and the creepiest carnival of all time! Rachel has a chance to join the secret Midnight Society. All she has to do is tell a truly terrifying story. But when the chilling events of her Tale of Mr. Tophat and the Carnival of Doom start to actually come true and her friends' lives are at stake, Rachel must face her fears and end Mr. Tophat's reign of terror.